Z-Score Model in Predicting Corporate Financial Distress of PETONE - Lim, Chee Chee (2017)
At the night on 15 January 2013, when the ticking clock on the office wall had sounded eight times, Arifin, the financial advisor of Petrol One Resources Berhad (PETONE) realised that it was 8 p.m. then. Arifin was still in his office cracking his head thinking of a method that he could use to examine the financial health of PETONE.This was the task assigned to him after meeting with PETONE’s chairman, Azmin, at 5.30 pm.During the meeting which lasted for half an hour, Arifin was assigned a task which he had to present the findings the following Tuesday on 22 January 2013 regarding the financial health of PETONE to identify (i) the first warning sign indicating that the company was getting into financial trouble, and (ii) the major causes that had led the company into distressed financial situation. This assignment was in response to the announcement made on 30 August 2012 to classify PETONE as a Practice Note 17 (PN17) company when PETONE had triggered one of the prescribed criteria under the main market listing requirements of Bursa Malaysia Securities Berhad (Bursa Securities).After thinking hard for two hours, finally he had decided to apply z-score model to analyse the financial health of PETONE. As such he could leave office now and the next day when he came in to work, he could start going through the financial reports of PETONE to collect the required data for the z-score model he intended to use to assess the financial health of PETONE.